Influence of the PtxRuIry electrocatalysts composition toward oxygen evolution and reduction reactions for unitized regenerative fuel cell. (26th July 2021) - Morales S., L.; Gochi-Ponce, Y.; Altamirano-Gutiérrez, A.; Fernández, A.M.
Abstract: Electrodes based on ternary electrocatalysts for the oxygen evolution and reduction reaction in a unitized regenerative fuel cell were proposed and evaluated. Five Ptx RuIry varying the amount of Pt and Ir were synthesized by chemical reduction. We analyzed the different Ptx RuIry physicochemical properties and their stability electrochemical in repetitive changes to oxygen evolution and reduction reaction in 0.5 M of H2 SO4 . Samples showed a low crystallinity associated with different phase formation and a high particle agglomerates with an increment of Pt. The stoichiometric ratio proposes as Pt3.5 Ru4.0 Ir1.5 was the most promising electrocatalyst, exhibiting a high transfer coefficient and a Tafel slope of −65 mV·dec −1 after repetitive measurements. Highlights: Different Ptx RuIry were synthesized by the chemical reduction method. Low crystallinity in the Ptx RuIry is associated with different phase formations. Repetitive electrochemical changes to ORR/OER in an acid medium were analyzed. Pt3.5 Ru4.0 Ir1.5 showed a more stable electrochemical activity for OER and ORR.